Novel finding: 2,4-Di-tert-butylphenol from streptomyces bacillaris ANS2 effective against mycobacterium tuberculosis and cancer cell lines - Kaari, Manigundan; Joseph, Jerrine; Manikkam, Radhakrishnan; Kalyanasundaram, Revathy; Sivaraj, Anbarasu; Anbalmani, Sivarajan; Murthy, Sangeetha; Sahu, Amit Kumar; Said, Madhukar; Dastager, Syed G.; Ramasamy, Balagurunathan (Applied Biochemistry and Biotechnology, 2023)
The aim of the present study is to identify actinobacteria Streptomyces bacillaris ANS2 as the source of the potentially beneficial compound 2,4-di-tert-butylphenol, describe its chemical components, and assess its anti-tubercular (TB) and anti-cancer properties. Ethyl acetate was used in the agar surface fermentation of S. bacillaris ANS2 to produce the bioactive metabolites. Using various chromatographic and spectroscopy analyses, the potential bioactive metabolite separated and identified as 2,4-di-tert-butylphenol (2,4-DTBP). The lead compound 2,4-DTBP inhibited 78% and 74% of relative light unit (RLU) decrease against MDR Mycobacterium tuberculosis at 100ug/ml and 50ug/ml concentrations, respectively. The Wayne model was used to assess the latent/dormant potential in M. tuberculosis H37RV at various doses, and the MIC for the isolated molecule was found to be 100ug/ml. Furthermore, the molecular docking of 2,4-DTBP was docked using Autodock Vinasuite onto the substrate binding site of the target Mycobacterium lysine aminotransferase (LAT) and the grid box was configured for the docking run to cover the whole LAT dimer interface. At a dosage of 1 mg/ml, the anti-cancer activity of the compound 2,4-DTBP was 88% and 89% inhibited against the HT 29 (colon cancer) and HeLa (cervical cancer) cell lines. According to our literature survey, this present finding may be the first report on anti-TB activity of 2,4-DTBP and has the potential to become an effective natural source and the promising pharmaceutical drug in the future.
Keywords: 2; 4-Di-tert-butylphenol; anti-cancer; Anti-tubercular; Molecular docking; Streptomyces bacillaris